(untitled) (Veterinary Science Development, 2015)
Listeria monocytogenes is an ubiquitous, intracellular pathogen which has been implicated within the past decade as the causative organism in several outbreaks of foodborne diseases. In this review, a new approach to molecular typing primarily designed for global epidemiology has been described: multi-locus sequencing typing (MLST). This approach is novel, in that it uses data that allow the unambiguous characterization of bacterial strains via the Internet. Our aim is to present the currently available selection of references on L. monocytogenes MLST detection methods and to discuss its use as gold standard to L. monocytogenes subtyping method.